Absorption-transmission-integrated frequency selective structure based on spoof surface plasmon polariton modes. (8th February 2019) - Wang, Chao; Li, Yongfeng; Feng, Maochang; Wang, Jiafu; Ma, Hua; Zhang, Jieqiu; Qu, Shaobo
Abstract: A method of engineering the frequency selective structure with absorption and transmission based on spoof surface plasmon polariton (SSPP) modes is proposed and demonstrated in this paper. High-efficiency transmission can be achieved based on SSPP modes coupling. Due to the electric field enhancement effect of the coupled SSPP on the metallic blade array, high-efficiency absorption can be achieved by the high loss of the FR4 dielectric substrate. To verify this method, the absorption-transmission-integrated frequency selective structure was designed using the metallic trapezoid structure, metallic fishbone structure and FSS. The metallic trapezoid structure can absorb the low frequency electromagnetic (EM) waves and the metallic fishbone structure can absorb the high frequency EM waves. Two absorption bands are respectively in C and Ku bands. The FSS can modulate the passband characteristic of the metallic trapezoid structure and metallic fishbone structure. High-efficiency transmission can be achieved in the middle of two absorption bands. At last, the absorption-transmission-integrated frequency selective structure was fabricated and measured to verify the feasibility of this method. It can be used for the electromagnetic windows of vessels.